(untitled) (Revista de Artes Marciales Asiáticas, 2019)
Martial arts such as Taekwondo and Gumdo are distinctive symbols of Korean culture. Its international dissemination is the outcome of a governmental policy sustained since the middle of the 20th century. The popularity of this training systems is associated with the idea that they instill fundamental values of Korean society, such as respect for authority and hierarchy, and the preeminence of collective over individual. In this paper we describe how such values are incorporated and reproduced in the daily practice of martial arts in Korea, by analyzing the rank system typical of these disciplines and the rites of passage needed for moving through this symbolically structured space. In doing so, we show some tensions and arrangements which arise from the confrontation between the values that martial disciplines incarnate and wider moral regimes. Specifically, how the teaching of martial arts in Korea contributes to the reproduction of gender inequalities, preserving a specific form of masculine domination.